PERENCANAAN PERSEDIAAN BAHAN BAKU BERDASARKAN METODE MRP (MATERIAL REQUIREMENTS PLANNING) - Yudha Astana, I Nyoman (Jurnal Ilmiah Teknik Sipil; Vol. 11, No. 2 Juli 2007)
Supply is goods or materials to fulfill specific purposes, i.e. to supply a production process of a product. The supply influences an operational cost. If supply management is not good, it will reduce the company’s profit. Many companies have a problem on their supply, they some times oversupply or even undersupply. These conditions will increase the production cost. Therefore, the supply management is needed to analyze and to find out an optimum inventory level. The requirement plan of the material is provided by MRP method which first estimates the total request for production in the future. The Moving Average with Linear trend and of Single Exponential Smoothing with Linear of Trend is applied for the demand forecasting. This method applied at PT. Torsina Redikon, using Lot For Lot (LFL), Fixed Period Requirement (FPR), and Fixed Order of Quantity (FOQ). The smallest expense found from Lot For Lot (LFL) that is Rp 9.652.434.320,00. Keywords: inventory planning, MRP Methods.
Keywords: PERENCANAAN PERSEDIAAN BAHAN BAKU BERDASARKAN METODE MRP (MATERIAL REQUIREMENTS PLANNING) Oleh: I Nyoman Yudha Astana Full Paper : Download Here ABSTRAK Abstrak: Persediaan adalah bahan atau barang yang disimpan, yang akan digunakan untuk memenuhi tu